Physical and electrochemical performances of novel tellurium composite films as anode applications in energy storage systems - Md Masud Rana; Mohammad Asaduzzaman Chowdhury; Md. Jonaidul Alam; Md. Rifat Khandaker; Yusuf Ali (Heliyon)
Portable electronic devices and electric cars use lithium-ion batteries, but clumping lithium alloys limit their lifespan. Due to their strong electronic conductivity, volumetric capacity, and high energy density, researchers are conducting research on electrochemical metal cells utilizing tellurium for high-performance batteries. Theoretically, lithium-tellurium batteries can improve energy densities three times more than lithium-ion batteries. However, metal-tellurium faces challenges such as low rate capability, unclear redox reactions, intermediate dissolution, and electrode volume changes. This study explores the enhancement of the energy storage capacity of next-generation batteries by fabricating coated electrode films as novel anodes from tellurium, silicon, and graphene. Physical, thermal, and morphological analysis of composite material are investigated by XRD, TEM, TGA, DSC, SEM, UV, and XPS analyses, revealing its rigidity as well as durability through its crystal structure alignment and thermal stability. In electrochemical analysis (CV) at various scan rates, samples that exhibit consistent and high specific capacity (Cp) values at different scan speeds (25, 50, and 100 mV/s) indicate excellent ability to store and maintain charge. Decreasing Cp values with increasing scan rates indicate that the speed of cycling limits the charge transfer kinetics and electrode performance. In EIS, the charge transfer resistances (Rct) for the pure Te, Te + Gr, Te + Si + Gr, and Te + Si samples are 759.07 Ω, 4.21 Ω, 36.39 Ω, and 164.90 Ω, respectively. The Te + Gr sample has the lowest Rct, indicating the best charge transfer efficiency at the electrode contact, whereas the Te + Si + Gr sample has a comparatively lower Rct, indicating better charge transfer kinetics. The combined result exhibits the synergistic impact of tellurium, silicon, and graphene in enhancing the energy storage capacity of future batteries across the industry.